Levels of plasma vitamins and elements in aborted ewes in Elazig region of Turkey - Naziroglu, M; Cay, M; Karatas, F; Çimtay, I; Aksakal, M; Eder, K (Verlag Harold Schubert, 1999)
The current study was to examine the levels of vitamin A, E, selenium, zinc, copper, phosphorous, magnesium and total protein in blood of aborted ewes. Aborted and control (non aborted) Akkaraman ewes were used from different regions of Elazig of Turkey. The levels of selenium, zinc, copper, phosphorus, magnesium, total protein, vitamin A and E were measured in plasma samples of aborted and control animals. Present findings showed that concentrations of vitamin E, selenium, copper, phosphorus, magnesium were significantly lower (P<0.05, P<0.001) in aborted ewes than in controls. However, there was no significant difference in zinc, vitamin A and total protein levels showed between the two groups. The results indicated that the levels of vitamin E, selenium, copper, phosphorus and magnesium were significantly lower in aborted owes than in control ewes in Elazig region and the high incidence of ewe abortion is believed to be due to deficiency of vitamin E, selenium, copper, phosphorus and magnesium.
19th Workshop on Macro Elements and Trace Elements -- DEC 03-04, 1999 -- FRIEDRICH SCHILLER UNIV, JENA, GERMANY
Keywords: Glutathione-Peroxidase; Habitual Abortion; Selenium; Lipoperoxides; Women